Morphological ciliary muscle changes associated with form deprivation-induced myopia. (April 2020) - Pucker, Andrew D.; Jackson, Ashley R.; McHugh, Kirk M.; Mutti, Donald O.
Abstract: Myopic children have larger ciliary muscles than non-myopic children, suggesting that the ciliary muscle may have an impact on or be affected by refractive error development. The guinea pig represents an attractive model organism for myopia development research. The purpose of the study was to investigate whether form deprivation-induced myopia in one or more strains of guinea pig causes thickening of the ciliary muscle as seen in human myopia. Thirty-nine guinea pigs were bred from in-house progenitors obtained from Cincinnati Children's Hospital (Cincinnati) and the United States Army (Strain 13). At 2–4 days of age the right eyes of animals were exposed to form deprivation for 7 days while the fellow eyes served as controls. Refractive error was determined with retinoscopy while vitreous chamber depth (VCD) and axial length (AL) were determined with A-scan ultrasound. Ciliary muscle characteristics (ciliary muscle length, cross-sectional area, volume, cell number, cell size, and smooth muscle actin concentration) were determined histologically with antibody labeling and analyzed according to whether the animal developed axial myopia (anisometropia > −2.00 D with VCD and/or AL differences > 0.1 mm) or was unresponsive. This analysis method yielded four groups with Group 1 having no induced myopia but with axial elongation (n = 11), Group 2 having myopia without vitreous or axial elongation (n = 8), Group 3 having myopia with either vitreous or axial elongation (n = 11), and Group 4 having myopia with both vitreous and axial elongation (n = 8). There were no post-treatment inter-ocular differences between strains or for the overall group of animals for any ciliary muscle variable; however, a higher response group number in multivariate ordinal regression was related to having a treated compared to fellow eye that had a lower smooth muscle actin concentration (p = 0.006), with a shorter ciliary muscle length (p = 0.042), and a less oblate eye shape (p = 0.010). Guinea pig ciliary muscle length and smooth muscle actin concentration were significantly less in the treated eyes of axially myopic animals suggesting that 7 days of form deprivation induced ciliary muscle cellular atrophy or inhibited ciliary muscle growth. Form deprivation myopia in the guinea pig does not result in the increase in ciliary muscle thickness associated with human juvenile and adult myopia. Highlights: Induced axial myopia in guinea pigs results inciliary muscle morphological changes that differ from human myopia. Induced ciliary muscle changes suggest atrophy or inhibited muscle growth. New guinea pig strains were described for myopia development research.